A Process Driven Dynamic Model for Petroleum Product Demand in Transportation Sector of India - Uttiya Bhattacharyya; R S Dhalla (International Journal of Supply Chain Management, 2014)
This paper proposes a dynamic process to identify factors influencing the demand of transport fuel in India. Factors like inter-fuel substitution by CNG, environmental concerns, economic outlook and price sensitivity must be incorporated in the demand estimation model. Differential subsidy in India on diesel and petrol affects its demand and the choice of vehicle ownership. A self designed questionnaire is used to survey and identify the factors affecting the demand for petrol and diesel. Multiple regression models are formulated for demand estimation of petrol and diesel with principal factors. Models are validated with real time data.